Exploring the Use of Flashcards to Improve Understanding of Flat Shapes in STEAM-Based Mathematics Learning in Elementary Schools - Amalia, Nindiana Eva Rosa; Mariana, Neni (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
Abstract: Mathematics learning in elementary schools often faces obstacles in understanding geometric concepts, especially flat shapes, due to limitations in the use of concrete and interactive media. This study aims to explore the use of flashcards in STEAM-based mathematics learning as an effort to improve fourth-grade elementary school students’ understanding of the concepts of sides, angles, and straight lines. The method used is a qualitative approach with a case study design, involving 14 fourth-grade students at SDN Lidah Wetan 4 Surabaya. Data were collected through participatory observation, semi-structured interviews, documentation, and field notes, then analyzed using the Miles and Huberman model. The results showed that the combination of flashcards with manipulative activities using toothpicks and plasticine within the STEAM framework was able to increase student engagement, facilitate concrete conceptual understanding, and encourage critical thinking, creativity, collaboration, and mathematical communication skills. These findings confirm that simple media can be innovatively optimized to strengthen mathematics learning in line with the demands of the 21st-century curriculum. This study provides practical contributions for elementary school teachers and opens opportunities for further research on other geometry materials and different grade levels. Keywords: Mathematics Learning, Flashcards, STEAM, Flat Shapes, Elementary School